OPTIMALISASI TATA KELOLA ASET TANAH PEMERINTAH DI KABUPATEN KUTAI KARTANEGARA - Nuzul Wahyu Insyori (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
This research is motivated by issues in the management of regional government land assets, which have not yet been optimized. These issues are indicated by the existence of uncertified assets, overlapping ownership, land controlled by the community, and unclear boundaries. The purpose of this study is to analyze the process of optimizing land asset management by the Land and Spatial Planning Agency of Kutai Kartanegara Regency using Suwanda’s (2013) theory, to identify supporting and inhibiting factors, and to formulate efforts to improve the effectiveness of regional government land asset management. This study employs a qualitative method with an inductive approach, in which the researcher acts as the main instrument. Data collection techniques include structured interviews, observation, and documentation. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing. The results show that the management of regional government land assets has been implemented systematically through stages of planning, budgeting, procurement, utilization, safeguarding, and supervision in accordance with applicable regulations. However, there are still obstacles such as limited human resources, facilities and infrastructure, as well as administrative issues, including unrecorded assets and community control over government-owned land. The main supporting factors include regulatory support, inter-agency coordination, and asset certification programs. In conclusion, land asset management in Kutai Kartanegara Regency has been carried out in accordance with existing regulations, but strengthening coordination, digitalizing asset data, and improving the capacity of personnel are necessary to achieve comprehensive optimization.